2022
DOI: 10.1530/eor-21-0092
|View full text |Cite
|
Sign up to set email alerts
|

Torsional deformities and overuse injuries: what does the literature tell us

Abstract: Overuse injuries imply the occurrence of a repetitive or an increased load on a specific anatomical segment which is unable to recover from this redundant microtrauma, thus leading to an inflammatory process of tendons, physis, bursa, or bone. Even if the aetiology is controversial, the most accepted is the traumatic one. Limb malalignment has been cited as one of the major risk factors implicated in the development of overuse injuries. Many authors investigated correlations between anatomical deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Future studies should therefore include a more complex multi-DoF model of the femorotibial and femoropatellar joints, including a detailed characterization of the articular contact geometry and the stabilizing passive soft-tissue constraints ( Lenhart et al, 2015 ; Marra et al, 2015 ; Dejtiar et al, 2020 ). A more detailed understanding of knee and patellar mechanics could be particularly important in the analysis of patients with miserable malalignment syndrome, in which an increased femoral anteversion and a concomitant outward tibial torsion can cause anterior knee pain, patellar maltracking and instability ( Eckhoff, 1994 ; Eckhoff et al, 1997 ; Bruce and Stevens, 2004 ; Stevens et al, 2014 ; Pagliazzi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should therefore include a more complex multi-DoF model of the femorotibial and femoropatellar joints, including a detailed characterization of the articular contact geometry and the stabilizing passive soft-tissue constraints ( Lenhart et al, 2015 ; Marra et al, 2015 ; Dejtiar et al, 2020 ). A more detailed understanding of knee and patellar mechanics could be particularly important in the analysis of patients with miserable malalignment syndrome, in which an increased femoral anteversion and a concomitant outward tibial torsion can cause anterior knee pain, patellar maltracking and instability ( Eckhoff, 1994 ; Eckhoff et al, 1997 ; Bruce and Stevens, 2004 ; Stevens et al, 2014 ; Pagliazzi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Powers (2003) and Stevens et al (2014) reported a correlation of increased femoral anteversion with patellofemoral pain, while increased femoral anteversion is also a known risk factor for patellofemoral instability ( Dejour and Le Coultre, 2007 ). Lower limb torsional malalignment is also one of the major risk factors implicated in the development of overuse injuries ( Pagliazzi et al, 2022 ). Femoral torsional and coronal deformities have previously been correlated with hip pain and labral damage ( Tönnis and Heinecke, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…This definition was the basis for comparison with other studies. All other associated studies agreed with Dr. James that MMS involves increased femoral anteversion and increased external tibial torsion [1][2][3]5,8,10,[12][13][14][15][16][17][18][19][20][21][22][23] . It was also mentioned that MMS often presents with squinting patella, patella alta, patellar instability, and an increased Q angle [1][2][3]5,8,10,[12][13][14][15][16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 63%
“…Other studies also specified that MMS may cause pronated feet, so this was included in the proposed definition 1,3,4,17,19,22,24 . Pes planus (flat feet) and the presence of genus recurvatum are both possible signs of this condition, so these were considered 1,3,5,18,19,23,25 . Studies have also shown that both genu valgus and genu varum can develop because of MMS as well 1,5,13,18,23,26 .…”
Section: Classificationmentioning
confidence: 99%
“…Many idiopathic torsional deformities seen in daily practice are minor and have little clinical signi cance. However, excessive malalignment can lead to an altered gait pattern, increased risk of falls, functional limitations, overuse injuries, joint pain and increased risk for clinical problems such as osteoarthritis [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%